THE PRINCIPLES OF ENVIRONMENTAL PROGRAM FORMATION FOR DISTRICT PLANNING - Pozdnyakov, Andrey Leonidovich (Journal of Applied Engineering Science, 2018)
On mesoterritorial level (schemes and projects of district planning) urban structures are studied and designed with much more detail, and because of the greater complexity of district planning spectrum of relationships between natural and anthropogenic components of the district is particularly rich. Therefore, urboecological tasks at this level include not only the special zoning of the territory, but the development of quite specific environmental and hygienic measures, including proposals for the establishment of systems for purification of air, water and soil, the allocation of the various security and sanitary protection zones, the development of green plantings of district, etc. At the same time, geographic, ecological and architectural-planning methods as well as technological and hygienic ones are equally applicable.